(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Dr. Mulk Raj Anand’s works, which center on the class’s struggle to make ends meet and theways in which the upper class and well-to-do members of society exploit and deny them anypossibilities, represent the Dalit and subaltern class of Dr. Mulk Raj Anand’s period in India realisticallyand compassionately. Mulk Raj Anand, a novelist who is passionate about social justice, has written anumber of works on the topic. His works have had a significant impact on the growth of Indian writing inEnglish. Simply put, Anand’s art is permeated with a voice that is insistent and strong yet muffled by theconstraining fabric of tradition and convention.